Perceptions of Television Journalists on the COVID-19 Pandemic in Indonesia - Musfialdy Musfialdy; Dadang Rahmat Hidayat; Siti karlinah; Uud Wahyudin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
COVID-19 is not the first outbreak to spread around the world. This flu disease, named by WHO as Coronavirus Disease (COVID-19), is caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Ironically, several studies on COVID-19 show that this virus is genetically engineered and is not the leading cause of death for the majority of COVID-19 patients. The COVID-19 pandemic has also triggered fear and panic in the community. This study aims to determine the perception of television journalists during the COVID-19 pandemic in Indonesia. This research was conducted in two Indonesian television media, namely iNews TV and Metro TV. This research used a qualitative case study methodology with a subjective paradigm. The research results showed that television journalists perceive the COVID-19 Pandemic as a real ongoing situation. Their perceptions are formed based on scientific knowledge, empirical experience, attention, and current information. The panic and fear of television journalists at the beginning of the pandemic occurred due to changes in interaction patterns and the adaptation process.